(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Khumaida N, Syukur M, Bintang M, Nurcholis W. 2019. Phenolic and flavonoid content in ethanol extract and agro-morphological diversity of Curcuma aeruginosa accessions growing in West Java, Indonesia. Biodiversitas 20: 656-663. Curcuma aeruginosa is a rhizomatous medicinal plant with beneficial pharmacological activities. The aim of this work was to analyze the agro-morphological, extract yield, and phenolic content of ten C. aeruginosa accessions which were collected from different locations in Indonesia. Cultivation was carried out in the open field in West Java of Indonesia using a completely randomized design. Qualitative and quantitative parameters were used to investigate agro-morphological traits. Total phenolic and total flavonoids contents were determined in ethanol extracts of samples. The plants were phenotypically diverse, in which there were significant variations among the ten C. aeruginosa accessions in number of leaves, plant height, number of shoots, fresh weight of rhizome, and dry weight of rhizome characters. Variability in the total phenolic and total flavonoid contents ranged from 29.08-46.92 mg GAE/g, and 21.31-33.81 mg QE/g, respectively. Six accessions had high phenolic content and extract yield. Therefore, these accessions could be utilized for commercial scale and also showed a high potency for medicinal plant breeding programs.